Globalised quests for assisted conception: Reproductive travel for infertility and involuntary childlessness - Whittaker, Andrea; Inhorn, Marcia C.; Shenfield, Francoise (Global public health, 2019)
The global movement of people across international borders to undergo assisted reproductive treatment is common, although there is little accurate data. In this article, we synthesise findings from our own empirical research on reproductive travel in addition to a review of clinical, ethical, legal, and regulatory complexities from studies on reproductive travel since 2010. Motivations for travel include legal and religious prohibitions; resource considerations; lack of access to gametes and reproductive assistors; quality and safety concerns; and personal preferences. Higher risks to mothers and children are associated with multiple embryo transfer and subsequent multiple and higher order pregnancies and the average older age of women undertaking reproductive travel. The potential exploitation of other women as providers of oocytes or surrogacy services, the lack of equity in access to assisted reproduction and the ambiguous legal status of children conceived from international reproductive travel are important ethical considerations. A range of significant legal issues remain given variable and limited international regulation. Scholarship on this trade necessarily engages with issues of power and gender, social inequities, global capitalism and the private decision-making of individuals seeking to form families. Research gaps remain given recent changes in the organisation, demands and destinations of the trade.